Is Education 4.0 a Sufficient Innovative, and Disruptive Educational Trend to Promote Sustainable Open Education for Higher Education Institutions? A Review of Literature Trends - Chaka, Chaka (Frontiers in Education, 2022)
The paper explored whether Education 4.0 is a sufficient innovative, and disruptive educational trend to promote sustainable open education for higher education institutions (HEIs). To investigate whether this is the case, the paper reviewed published journal articles that provide real-world, empirical applications of Education 4.0 in the higher education (HE) sector that are intended to promote and realize the United Nations’ (UN) sustainable development goals (SDGs). In particular, the paper focused on aspects of SDGs related to education (or to sustainable open education), and which had relevance to the HE sector. Three of the findings of this review study are worth mentioning. First, real-world Education 4.0 is confined to certain countries, and is more concentrated to a few countries and to a few HEIs. Second, ten sets of Education 4.0 technologies were classified as a disruptive, scalable, and sustainable, and as holding the prospect to promote sustainable open higher education in accord with the UN’s SDGs. Thirdly, most of the soft-skill affordances cited (especially the 21st century skills cited), lend themselves well as stylized facts as they predate Education 4.0 and are, thus, are not exclusive to it.